Pemberdayaan Santri dalam Pemeliharaan Kebersihan dan Pengembangan Potensi Wisata Pesantren (Studi Kasus Pesantren Musthafawiyah) - Fauziah Nasution (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
The existence of the Mustahfawiyah pesantren in the field of education and da'wah for more than a century and its uniqueness has made this pesantren "global". But in fact with santri reaching 12,578 people the realization of Islamic teachings about cleanliness experienced serious obstacles. On the other hand this boarding school turned out to have high tourism potential, but it is unfortunate that it has not been managed properly. The empowerment of santri through Participatory Action Research, turned out to be able to change the awareness of santri about cleanliness maintenance and development of Islamic boarding school tourism potential. This activity involved the MADINA Regency government; Office of Environment, Tourism Office, District and village government, and pesantren alumni who are members of the Arbituren Musthafawiyah Family Organization (KAMUS).